Revitalization of Sustainable Water Resources Policy in the Framework of Regional Autonomy in Indonesia - PAMBUDI, Andi Setyo (Indonesia Strategic Sustainability, 2025)
Indonesia’s water resource governance is facing a multifaceted crisis exacerbated by a decentralized administrative structure. Although regional autonomy was envisioned to enhance local responsiveness, it has instead fostered policy fragmentation, weak inter-jurisdictional coordination, and increasing vulnerability of river ecosystems. This paper addresses these systemic challenges by analyzing the underlying governance failures and advancing a strategic framework for revitalizing sustainable water policy. The study employs a qualitative-descriptive methodology through comprehensive literature review and thematic analysis, incorporating comparative insights from international best practices. Findings reveal that effective water governance requires harmonization of regulatory frameworks between central and local governments, institutional capacity-building at the subnational level, integration of spatially enabled data systems, and the institutionalization of inclusive community participation. Policy recommendations emphasize the establishment of legally mandated river-basin-based coordination bodies, the realignment of legal instruments toward ecological justice, the adoption of performance-based fiscal incentives for conservation, and the empowerment of local stakeholders in planning and oversight mechanisms. Ultimately, the revitalization of Indonesia’s water policy demands a systemic, ecologically grounded, and multilevel governance approach—essential for ensuring national water security and advancing sustainable development under the regional autonomy regime.